(untitled) (Revista de Ensino em Artes, Moda e Design, 2020)
This article derives from a course conclusion paper, which aimed to analyze the signs of fashion present in the school environment, understanding how it is perceived, establishing possible characterizations of exclusion, identification and inclusion. In this sense, the study was classified as applied in nature, and was understood as a quali- tative and exploratory research, taking place in a bias of Fashion, Peircean Semiotics and Education. The results showed that fashion materializes in the school space as a means of communication, because it is through it that students know each other as part of the environment. As well as fashion mediates relationships within this space.